Protective Effects of Curcumin and Resveratrol on Kidney Tissue on Cadmium-induced Oxidative Stress in Rats - Suat Cakina; Latife Ceyda İrkin; Şamil Öztürk (Gazi Medical Journal)
Objective: Cadmium (Cd) is a well-known widespread environmental pollutant and is not rapidly excreted by the kidneys; instead, it accumulates and causes kidney damage. This study aimed to compare the effects of antioxidant curcumin and resveratrol on antioxidant defense in Cd-induced rat kidney tissue. Methods: In the study, 36 (200-250 gr) Wistar albino rats were divided into 6 (n=6) groups. Group 1: control; group 2: CdCl2; group 3: curcumin; group 4: CdCl2 + curcumin; group 5: resveratrol; group 6: CdCl2 + resveratrol. At the end of the experiment, malondialdehyde (MDA), total oxidant capacity (TOC), and total antioxidant capacity (TAC) activities were measured in kidney tissues. Results: In the CdCl2-treated group, oxidative stress index (OSI), TOC, and MDA levels increased compared with the control group, and TAC values decreased (p<0.05). In the case of resveratrol or curcumin administered with Cd, TAC levels increased, MDA levels, and OSI values decreased compared with the group administered only Cd (p<0.05). Conclusion: Both resveratrol and curcumin may have protective effects in the kidneys against CdCl2-induced oxidative damage.